Identifikasi dan uji efektivitas rizobakteri dalam meningkatkan hasil tanaman kacang tanah - Khamdan Khalimi; Wayan Anik Leana (Jurnal AGRO, 2023)
In order to increase groundnut productivity, it is necessary to find agents that can  improve  the  growth  and  yield  of it.  This  study  was  done  to determine the potential use of rhizobacteria to promote the growth and increase the yield of groundnut under green house experiment. The research was conducted in the plant disease laboratory, Faculty of Agriculture, Udayana University, in June 2022-January 2023. Five isolates of rhizobacteria namely FN1, FN2, FL3, FL4, and FL5 were tested for their effectiveness in promoting the growth, increase the yield, and protein content of groundnut. Molecular identification based on 16S rRNA gene sequence showed that FN1 and FL5 were similar to Klebsiella pneumonia with the similarity level at 98%. FN2 was similar to Klebsiella variicola with 99% similarity, FL3 was similar to Proteus mirabilis with 100% similarity, and FL4 wassimilar to Providencia rettgeri with 99% similarity. Rhizobacteria treatments significantly improved the groundnut growth, in which plant height, dry weight of shoot, dry weight of root, chlorophyll content, and the number of nodule significantly (p<0.05) higher compared to control. Yield component such the number of pod per plant, weight of pod per plant, water content and protein content in the seed of treated plants were significantly higher than control. These rhizobacteria may be further developed as plant growth promoting agents to increase the yield  and protein content of groundnut.ABSTRAK Pemanfaatan mikroba yang bisa meningkatkan pertumbuhan dan hasil kacang tanah sangat penting untuk meningkatkan produksi. Penelitian ini menguji tentang potenis rizobakteri untuk meningkatkan pertumbuhan dan hasil kacang tanah yang dibudidayakan pada greenhouse. Penelitian dilakukan di lab penyakit tumbuhan, fakultas pertanian universitas udayana, pada bulan Juni 2022-januari 2023.  Lima isolat rizobakteri: FN1, FN2, FL3, FL4, dan FL5 telah diujikan untuk mengetahui kemampuan dalam meningkatkan pertumbuhan, hasil serta kandungan protein kacang tanah. Analisis molekuler berbasis 16S rRNA menunjukkan isolat FNI dan FL5 memiliki 98% kemiripan dengan Klebsiella pneumonia. Isolat FN2 memiliki 99% kemiripan dengan Klebsiella variicola, isolat FL3 mirip dengan Proteus mirabilis pada tingkat 100%, dan isolat FL4 memiliki 99% kemiripan dengan Providencia rettgeri. Perlakuan dengan isolat rizobakteri menunjukkan hasil yang signifikan (p<0.05) pada pertumbuhan kacang tanah seperti tinggi tanaman, berat kering brangkas, berat kering akar, kandungan klorofil daun dan jumlah bintil akar dibandingkan dengan kontrol. Jumlah polong, berat polong per tanaman, kadar air dan kandungan protein pada tanaman juga menunjukkan hasil yang lebih tinggi dibanding kontrol. Hal ini menunjukkan rizobakteri potensial dikembangkan untuk meningkatkan pertumbuhan, hasil dan kandungan protein kacang tanah.